2019
DOI: 10.1101/790097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vector bionomics and vectorial capacity as emergent properties of mosquito behaviors and ecology

Abstract: AbstractMosquitoes are important vectors for pathogens of humans and other vertebrate animals. Some aspects of adult mosquito behavior and mosquito ecology play an important role in determining the capacity of vector populations to transmit pathogens. Here, we re-examine factors affecting the transmission of pathogens by mosquitoes using a new approach. Unlike most previous models, this framework considers the behavioral states and state transitions of adult mosquitoes through … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The relative abundance of these vectors has been mapped across Africa by a previous study, which showed that insecticide-treated net and IRS use affect the relative abundance of these species ( 35 ). Variation in the behavior of these vectors also influences how likely it is that they come into contact with indoors, insecticide-based interventions and, ideally, this variable should also be considered alongside insecticide resistance ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of these vectors has been mapped across Africa by a previous study, which showed that insecticide-treated net and IRS use affect the relative abundance of these species ( 35 ). Variation in the behavior of these vectors also influences how likely it is that they come into contact with indoors, insecticide-based interventions and, ideally, this variable should also be considered alongside insecticide resistance ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, mosquito population densities are rarely measured directly, but the number of mosquitoes per human is assumed to be directly proportional to the human-biting rate (HBR) (defined as the number of bites, per person, per day). Recently, several new mathematical models of adult behaviors and ecology have been developed to estimate the effect sizes of vector control on malaria transmission [6][7][8][9]. Some of these new models consider complex feedbacks and population dynamic thresholds that Macdonald's analysis ignored and they show that vector control could have large, nonlinear effects on mosquito population densities [5,10].…”
Section: Mosquitoes and Malaria Transmissionmentioning
confidence: 99%
“…With that in mind, we consider the evolution of formulas for VC and extensions of it as cases of a single motivating concept: VC is defined to be the number of infective bites arising from all the mosquitoes biting a single human on a single day, as if the human was perfectly infectious. If appropriate, VC could thus be computed as an expectation for each individual on any day [9].…”
Section: Box 2 Formulas For Vectorial Capacity (Vc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative probability of transmission following partial and full blood feeding is unclear, but increased partial blood feeding could negatively affect the epidemiological impact of the product if the probability of transmission is similar to what it is with full blood feeding [25]. Conversely, an increase in number of feeds could be accompanied with increased mortality due to the risks involved with blood feeding, which would further enhance the impact of the SR [26][27][28]. How such hazards differ in response to product exposure remains to be investigated.…”
Section: Plos Computational Biologymentioning
confidence: 99%